The gesture's narrative : contemporary music for percussion - Aroso, Nuno Mendes Moreira (2016)
Musical performance gestures are recognized by the majority of theoreticians as a critical factor of a musical performance. The aim of the musical performance may consist in not only communicating the musical signs that form a musical piece, but conveying the meaningful succession of gestures, facial expressions and body movements. This meaningful succession, or otherwise the “gesture´s narrative” is assumed to be quite important for the process of directing the audience towards the intended interpretation. Recording music allowed audiences to listen to music without having to go to a musical event for this purpose. On the one hand, this made the listening experience more intense, allowing to concentrate on the aural information exclusively, but, on the other hand, it also imposed restrictions on people’s perception, as the syncretic listening and seeing experience became separated into constituents. Gestures can be considered as operating features of a person’s perception-action system. It presupposes significance of a meaning that involves more than just a physical movement. Movements can be subdivided into specific patterns and conceptualized. Conceptualized gestures are kept in people’s minds as single units, and the subdivision operations are carried out both by performers and the audience. Musical communication through gestures is therefore not about movement only, it should be viewed as structured interactions. For this research, solo percussion contemporary music performance will be analyzed. Overall, percussive music performance is extremely wide, and is accompanied by bright visual images provided by musicians themselves. From this perspective, observation over percussionists’ playing manner and it´s audience provides the researcher an opportunity to understand a narrative ability of music through musicians’ gestures. The quantitative research design divided in three experiments was chosen for the purpose of this study, which can be referred to as the description of the objective reality by using numbers in order to construct meaningful models reflecting various relationships between objects or phenomena. These numerical entities are not the reality itself, but a way of representing it. Moreover, the chosen experimental design gives an opportunity to not only establish the existence of certain effects of one variable on the other one, but also study the magnitude of these effects, considering the major two research questions: Is it possible to detect a percussive gesture’s narrative ? How does the percussive gesture influences the perception of musical narrative?